2009
DOI: 10.1158/0008-5472.can-09-1106
|View full text |Cite
|
Sign up to set email alerts
|

Dual Therapeutic Efficacy of Vinblastine as a Unique Chemotherapeutic Agent Capable of Inducing Dendritic Cell Maturation

Abstract: Our recent unbiased functional screen of 54 chemotherapeutic drugs unveiled striking heterogeneity in their effects on dendritic cells (DC). Most notably, vinblastine (VBL) was found to induce phenotypic and functional maturation of DCs in vitro. Here, we sought to determine whether VBL exhibits ''dual'' therapeutic efficacy in living animals by directly killing tumor cells and by boosting host immunity via DC maturation. Local injection of VBL in a low dose into the skin of C57BL/6 mice induced in situ matura… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(72 citation statements)
references
References 41 publications
(51 reference statements)
2
69
1
Order By: Relevance
“…26 Notably, vinblastine at low concentrations (0.1-1 mM) induces phenotypic and functional maturation of DCs in vitro and in vivo, when injected into the skin of mice, by triggering in situ maturation of skin-resident DCs and by boosting humoral and cellular immune responses. 27 A recent study on human 6-sulfo LacNAc þ (slan) DCs, a major subpopulation of human blood DCs, showed that doxorubicin impairs the ability of these cells to produce proinflammatory cytokines and to activate T lymphocytes and NK cells, whereas methotrexate and paclitaxel sustain their effector properties. 28 Cytotoxic chemotherapy can affect DC activities also through indirect mechanisms.…”
Section: Effects On the Innate Immune Systemmentioning
confidence: 99%
“…26 Notably, vinblastine at low concentrations (0.1-1 mM) induces phenotypic and functional maturation of DCs in vitro and in vivo, when injected into the skin of mice, by triggering in situ maturation of skin-resident DCs and by boosting humoral and cellular immune responses. 27 A recent study on human 6-sulfo LacNAc þ (slan) DCs, a major subpopulation of human blood DCs, showed that doxorubicin impairs the ability of these cells to produce proinflammatory cytokines and to activate T lymphocytes and NK cells, whereas methotrexate and paclitaxel sustain their effector properties. 28 Cytotoxic chemotherapy can affect DC activities also through indirect mechanisms.…”
Section: Effects On the Innate Immune Systemmentioning
confidence: 99%
“…Although the cancer cell growth-inhibitory properties of dolastatins are several-fold greater than those of vinblastine, we included the latter agent into our experimental set-up based on previously published data showing its capacity to mature DCs (15,16). Following 24-hour culture of SP37A3 cells in the presence of dolastatin 10, dolastatin 15, vinblastine, or LPS, we determined the surface expression of the DC maturation markers CD80, CD86, CD40, and MHC-II ( Fig.…”
Section: Dolastatins Trigger Maturation Of Dcsmentioning
confidence: 99%
“…Nevertheless, only a few studies have been reported that have investigated the capacity of antitumor therapeutics to improve DC function. Recent work has identified several cytotoxic agents, including the mitotic spindle inhibitor vinblastine, as potent activators of DC maturation (14)(15)(16). Although the underlying mechanism is still poorly defined, these data clearly highlight a previously unrecognized immunostimulatory activity for vinblastine.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Second, multiple chemotherapeutics can directly stimulate antitumor immunity, 1,4 either by potentiating the activity of immune effectors (e.g., vinca alkaloids have been shown to promote the maturation of dendritic cells (DCs)) or by antagonizing immunosuppressive cells (e.g., cyclophosphamide reportedly depletes/inhibits regulatory T cells). 9,10 ICD has been operatively defined as a cell death modality that elicits a protective immune response against dead-cell antigens, implying that the immunogenicity of cell death can be monitored in appropriate vaccination assays. 2,11,12 Thus, the subcutaneous injection of cancer cells that are succumbing to ICD, but not of cells undergoing conventional apoptosis or necrosis, elicits a T-cell-mediated immune response protecting histocompatible mice against a subsequent challenge with tumor cells of the same type.…”
mentioning
confidence: 99%